FORMULATION AND PROXIMATE ANALYSIS OF SWEET POTATO POWDER INCORPORATED MILLET CAKE - A.Marithangam; Dr.M.S. Rubha; S. Charu Nivedha (The Bioscan, 2026)
The study involves formulation of a sweet potato powder mix with kodo millet (KM) flour at different concentrations